Disaster Medicine A Case Based Approach - MacGarty, David; Nott, David (Springer London : Imprint: Springer, 2013)
Whether switching on the TV, picking up a newspaper or simply logging on to the internet, one is constantly faced with images of natural disasters, conflict and human suffering. Humanity has experienced these problems throughout time and we have evolved methods and mechanisms for alleviating suffering, from trauma care following a traffic accident to international pacts and the Millennium Development Goals. In exploring such diverse cases of aid intervention, Disaster Medicine: A Case Based Approach provides interesting, easily accessible content and context for understanding disaster medicine and global health. In each case the reader will be put in the position of the decision maker and as in real life some of the cases will portray success and some will show failure. It is hoped the reader will consider the issues and problems for themselves and perhaps consider things they would choose to do differently. Written by a team of experts with extensive experience in the field and a progressive perspective Disaster Medicine: A Case Based Approach is a valuable text for students and professionals of disaster medicine.